Use of biomass fuels predicts indoor particulate matter and carbon monoxide concentrations; evidence from an informal urban settlement in Fort Portal city, Uganda - Winnifred K. Kansiime; Richard K. Mugambe; Edwinah Atusingwize; Solomon T. Wafula; Vincent Nsereko; Tonny Ssekamatte; Aisha Nalugya; Eric Stephen Coker; John C. Ssempebwa; John Bosco Isunju (BMC, 2022)
Abstract Background Poor indoor air quality (IAQ) is a leading cause of respiratory and cardiopulmonary illnesses. Particulate matter (PM2.5) and carbon monoxide (CO) are critical indicators of IAQ, yet there is limited evidence of their concentrations in informal urban settlements in low-income countries. Objective This study assessed household characteristics that predict the concentrations of PM2.5 and CO within households in an informal settlement in Fort Portal City, Uganda. Methodology A cross-sectional study was conducted in 374 households. Concentrations of PM2.5 and CO were measured using a multi-purpose laser particle detector and a carbon monoxide IAQ meter, respectively. Data on household characteristics were collected using a structured questionnaire and an observational checklist. Data were analysed using STATA version 14.0. Linear regression was used to establish the relationship between PM2.5, CO concentrations and household cooking characteristics. Results The majority (89%, 332/374) of the households used charcoal for cooking. More than half (52%, 194/374) cooked outdoors. Cooking areas had significantly higher PM2.5 and CO concentrations (t = 18.14, p ≤ 0.05) and (t = 5.77 p ≤ 0.05), respectively. Cooking outdoors was associated with a 0.112 increase in the PM2.5 concentrations in the cooking area (0.112 [95% CI: -0.069, 1.614; p = 0.033]). Cooking with moderately polluting fuel was associated with a 0.718 increase in CO concentrations (0.718 [95% CI: 0.084, 1.352; p = 0.027]) in the living area. Conclusions The cooking and the living areas had high concentrations of PM2.5 and CO during the cooking time. Cooking with charcoal resulted in higher CO in the living area. Furthermore, cooking outdoors did not have a protective effect against PM2.5, and ambient PM2.5 exceeded the WHO Air quality limits. Interventions to improve the indoor air quality in informal settlements should promote a switch to cleaner cooking energy and improvement in the ambient air quality.